The Effect of HR Relational Strategy and Transactional Strategy on Supply Chain Performance: The Moderating Role of Environment Orientation - Roespinoedji, Djoko; Faritzal, Adam; Sudrajat, Asep; Ahmed, Umair; Oktari, Sari Dewi (International Journal of Supply Chain Management, 2019)
The purpose of this study is to examine the effect of relational strategies and transactional strategies in order to determine the performance of supply chain management of Indonesian servicing sector through the moderating role of environment orientation. This research was done quantitatively. Questionnaire were Adapted to collect the data and random sampling technique was used. The sampling size was of 200. PLS3 software was applied to analyze the data. The findings of the study showed that the association of the basic strategies in terms of relational and transactional has a tendency to affect the performance of â€œsupply chain managementâ€ significantly and positively. The HRM organization adds to the assurance of practices inside the supply chain, both operationally and deliberately through the moderating role of â€œenvironment orientationâ€. Reconciliation of environmental issues in the supply chain assumes extremely noteworthy job in deciding the productivity and viability inside the supply chain management.